HUMAN DIGNITY AND RIGHTS VIOLATIONS AT A HORA DA ESTRELA - Oliveira, Flaviana de Freitas [UNESP]; Klein, Ana Maria [UNESP] (Univ Taubate, 2020)
The novel A Hora da Estrela, by Clarke Lispector, narrates the life of Macabea, whose rights are violated daily. The narrative leads us to think about the importance of dignity and the application of Human Rights. This work analyzes how the theme is approached in the novel, through the protagonist's experiences. The novel explains violations of the rights of women, children, food, work, affection, equality, freedom, among others. Clarice Lispector opens up the lack of human dignity in the life of the protagonist, who plays a victim role in society. Thus, it is understood the importance of the individual to transpose the victim's position and occupy the position of subject of rights, aware of the demands to be made in favor of dignity. Through analysis, we concluded the importance of the work by realistically exposing the routine violations of human rights in our society.
Keywords: Human rights; Dignity of human person; Literature; Clarice Lispector; Violation of rights